Diplomatic judicial immunity - Alaneed, Mohammad Zaid (Revue jurisprudence, 2019)
Diplomatic immunity is a form of legal immunity that ensures diplomats are given safe passage and are considered not susceptible to lawsuit or prosecution under the host country's laws, with the Vienna Convention on Diplomatic Relations, Diplomatic agents enjoy an almost absolute immunity from the jurisdiction of the receiving States during their term of office,The immunity from the criminal jurisdiction of the receiving State has an absolute character: there are no exceptions. This absolute immunity concerns all possible minor offences as well as grave crimes, such as the crimes against humanity.It is important to note that the immunity and inviolability of diplomatic agents do not stand in the way of investigation by the receiving State into allegations of abuse. The mere issuance of an order to investigate charges of abuse against diplomatic agents in function does not infringe the diplomatic immunity or inviolability.